Personalisation of Education in Contexts Policy Critique and Theories of Personal Improvement - Mincu, Monica E.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
This volume addresses personalisation, a key education policy in England and a key issue identified by the OECD for the schools of the future. The central questions addressed are: Which are the main theoretical perspectives on personalisation? Which are the policy strategies in different contexts? Which ingredients and theories of personalisation as legitimated knowledge from abroad are locally adopted and adapted in different countries? What are the meanings and purposes of personalisation? Why does it come paradoxically to be implemented by teachers through grouping by ability? Which alliances between the public and the private sectors are proposed? Leading scholars in the comparative education field as well as scholars committed to understanding the design and substance of education processes and politics, such as Michael Fullan, Chris Watkins, Michael Peters, Michael Fielding, Giorgio Chiosso, Ruth Deakin Crick, Ferran Ferrer, and Baocun Liu, engage with personalisation from a plurality of theoretical frameworks and in relation to many national contexts. The volume, prefaced by Mark Ginsburg, presents two main perspectives which are simultaneously at work. In the first, personalisation is assessed as a recent and global education policy, in line with the current restructuring reforms of State administration worldwide. In the second perspective, personalisation is assumed to be not only a matter of recent education policy regarding school clients and their choices, but foremost a pedagogical theory, a reassembly of old and new pedagogical approaches under new reform discourses. The volume edited by Monica Mincu offers a remarkable map of the theoretical understandings which inform different educational politics and school practices. Personalisation tends to legitimising forms of autonomy and a flexible educational relationship and thus its connection to standardisation represents a salient issue of this work. Luciano Benadusi, University of Rome Moving from teaching/learning theories to theoretical, critical, historical and religious arguments about schooling and its reforms, the various contributions provide impressive insights into the possibilities and limits of personalization for school innovation. The reader is engaged in a dialogue about the specifics of personalization as a reform focus and the historical, social and comparative complexities in which such efforts are bound. Thomas S. Popkewitz, University of Wisconsin-Madison The volume represents a significant opportunity to engage with the possibilities of personalized/individualized learning environments. It is our duty to provide our children with such positive learning contexts, and over the last thirty years we have focused considerable effort on this area in Japan. Koji Kato, President of the Japanese Society of Education for Individual Development
Keywords: Education; Education; Education (general).